PEMILIHAN MODEL REGRESI SPASIAL PADA TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA TENGAH - Nurika Nidyashofa; Moh. Yamin Darsyah (Program Studi Statistika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Muham, 2020)
Unemployment is a condition where someone who is included in the labor force wants to get a job but has not yet got it. For most people, losing a job is a condition where a person's standard of living has decreased. In Central Java the Open Unemployment Rate is high as seen from the influence of the number of labor force, the last education completed and the Human Development Index (HDI). Regression is an analysis used to measure the presence or absence of a correlation or relationship between variables. A model that can explain the relationship between an area and its surroundings is a spatial model. In spatial regression there are six models, namely SAR, SEM, SDM, SDEM, SAC and SAC-Mixed. This study will compare the results of the spatial regression analysis model using a Queen Contiguity weight. The best model obtained is SAC Mixed by looking at the smallest AIC value, namely 61,111